Evaluation of microstructure and mechanical properties resulting from gas nitriding process for different types of steel - Mohammed, Faras Q.; Ahmed, Ibrahim Abd L-Kareem; Fyayyadh, Sameer Khalaf (Zielona Góra: Uniwersytet Zielonogórski)
This work investigates the effect of the gas nitriding process on the surface layer microstructure and mechanical properties for steel 37, tool steel X155CrVMo12-1 and stainless steel 316L.
Keywords: AISI 316L; gas nitriding; micro-hardness; steel 37; X155